Multimedia based on science environment technology and society: The needs analysis human anatomy physiology learning - Nuril Hidayati; Farizha Irmawati (STKIP Persada Khatulistiwa Sintang, 2020)
The importance of information regarding the learning process is to be able to identify the main problems and provide the right solutions according to the predetermined graduate competency standards. This study aims to provide solutions to learning problems in the form of appropriate teaching materials in terms of users and the curriculum. The research method used is descriptive quantitative research through a survey with a research sample of 32.5% of the population or 26 students. The instruments used were questionnaires and interview transcripts. Data analysis was carried out with a student questionnaire, the percentage was calculated and will be explained while the interview transcripts were analyzed descriptively, 57.1% of students need teaching materials, 52.4% need teaching materials with specific learning approaches and models. The results showed that it is necessary to make improvements in the aspects of the learning model, mastery of 21st-century knowledge and skills, and the learning media used. Therefore, teaching materials are needed that include learning activities characterized by learning approaches or models, conceptual descriptions according to content standards, and evaluations that can develop higher-order thinking skills.Keywords: Higher education, human anatomy physiology, multimedia learning, SETS